Stability of the North Spur at Muskrat Falls - Bernander, Stig; Elfgren, Lennart (Luleå tekniska universitet, Byggkonstruktion och brand, 2019)
The paper presents the geotechnical background to one of the stability problems regarding the North Spur dam wall: This land was formed in the regression of the sea during and after the last ice age with deposits of multiple layers of silty sands and silty sandy clays that formed the valleys and plains that are now above sea level. Some of these layers, deposited thousands of years ago in post-glacial times, are vulnerable to liquefaction when they are disturbed. These conditions have in the past repeatedly caused slides along the banks of the Churchill river. In the current paper, a specific type of possible progressive failure – the most dangerous one in respect of the safety of the North Spur – is discussed. This type of landslide development may be caused by the rising water pressure, when - or after - the dam is impounded. As will be explained, such a slide could force part of the North Spur ridge to slide along a failure surface sloping East-wards into the deep river whirlpool downstream of Muskrat Falls. In the following, we provide a brief overview of the geotechnical background behind our concerns, also discussing methods of mitigating the risk of the kind of slope failure in question. Hence, we propose measures such as compacting the soil by piling or by methods of grouting and drainage. We also suggest the need for an expert Advisory Panel to look further into the long-term safety of the North Spur.